2021
DOI: 10.3389/fonc.2021.673378
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Versus Apatinib Both Combined Transarterial Chemoembolization for Hepatocellular Carcinoma With Portal Vein Tumor Thrombosis: A Comparative Retrospective Study

Abstract: ObjectiveTo compare the efficacy and safety of transarterial chemoembolization (TACE) combining with sorafenib or apatinib for hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT).MethodsFrom June 2015 to March 2020, a total of 89 consecutive advanced HCC patients with PVTT who were treated with sorafenib-TACE (S-TACE) or apatinib-TACE (A-TACE) in our center were enrolled. The overall survival (OS), time to progression (TTP), tumor response, and adverse events in the two groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Subsequently, 109 review articles, 102 published abstracts or conference proceedings, 128 unrelated topics, and four articles without a study endpoint (PFS or OS) were excluded. Finally, 39 cohort studies and two RCTs were included in the network meta-analysis [ 10 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The PRISMA flow diagram is presented in Supplementary Material S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 109 review articles, 102 published abstracts or conference proceedings, 128 unrelated topics, and four articles without a study endpoint (PFS or OS) were excluded. Finally, 39 cohort studies and two RCTs were included in the network meta-analysis [ 10 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The PRISMA flow diagram is presented in Supplementary Material S2 .…”
Section: Resultsmentioning
confidence: 99%
“…It remains controversial whether treatment with TACE plus apatinib prolongs the survival of patients with uHCC when compared with TACE plus sorafenib. A multicenter retrospective study revealed that TACE–apatinib yielded shorter PFS than TACE-sorafenib and no statistical difference in OS [ 21 ], whereas another study demonstrated that TACE plus sorafenib and TACE plus apatinib exhibited comparable prognosis for HCC patients with PVTT [ 20 ]. Our network meta-analysis showed that TACE plus apatinib resulted in significantly improved OS compared with TACE plus sorafenib, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13–16 Moreover, compared with TACE combined with sorafenib, TACE with apatinib exhibited a comparable prognosis for advanced HCC. 17 , 18 Compared with c-TACE plus apatinib, DEB-TACE plus apatinib may increase the intratumor drug concentration and result in more sustained drug release, resulting in a better treatment response and long-term survival. Few studies are currently reporting differences in the treatment of DEB-TACE and c-TACE combined with apatinib for HCC patients, and there is no research developing and validating the predictive model for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pazopanib is a small-molecule inhibitor of a variety of protein tyrosine kinases, with potential antitumor activity [ 48 ]. Sorafenib works by stopping the progression of cancer and blocking the therapeutic replication of potentially malignant cells [ 49 ]. Nintedanib is a small-molecule kinase inhibitor that competitively inhibits both non-receptor tyrosine kinases and receptor tyrosine kinases, and these inhibitory effects increase fibroblast proliferation, migration, and transformation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%